Crakenstein’s Brave New Pandemic World: The Place of Art, Science, and Storytelling - Pires de Souza, Renata (Abusões, 2021)
The present article aims at examining the place of art, science, and storytelling in Margaret Atwood’s Oryx and Crake (2003), comparing the novel to Mary Shelley’s Frankenstein (1818) and Aldous Huxley’s Brave New World (1932), mainly in what concerns some characters who are on the margins. In this context, scientific knowledge set against humanistic knowledge is the generating principle of social inequalities, and people concerned with arts are relegated to an inferior place. In the three novels, those who value words amid the techno-scientific developments of society are condemned to live alone for not fitting in. However, Oryx and Crake presents a possible rereading of Shelley’s and Huxley’s works, leading the central character to a less tragic closure, even though still in a devastated landscape. Ironically, in the aftermath of a pandemic, when the rules of science do no longer apply, it is a “words person” who survives, embracing his existence all through the act of storytelling. Atwood’s novel, therefore, celebrates and updates the classics in some way, transposing them to a brand-new universe, where – through her apocalyptic visions – it is also possible to make a parallel with the new coronavirus pandemic that we have faced in the real scenario.